2010
DOI: 10.1017/s0960129509990259
|View full text |Cite
|
Sign up to set email alerts
|

Turing universality of the Biochemical Ground Form

Abstract: We explore the expressive power of languages that naturally model biochemical interactions with relative to languages that naturally model only basic chemical reactions, identifying molecular association as the basic mechanism that distinguishes the former from the latter. We use a process algebra, the Biochemical Ground Form (BGF), which extends with primitives for molecular association CGF, a process algebra proved to be equivalent to the traditional notations for describing basic chemical reactions. We firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…where it was shown that a Turing machine could be simulated by a chemical reaction network with a small probability of error. Although not surprising, this result is in sharp contrast to the discrete semantics of reaction systems which are not Turing complete without either the tolerance of a small probability error [17], or the addition of other mechanisms such as the unbounded dynamic creation of membranes [2,38,9], or the presence of polymerization reactions on an infinite universe of polymers [10] or DNA stacks [40].…”
Section: Definition 2 ([48])mentioning
confidence: 83%
See 1 more Smart Citation
“…where it was shown that a Turing machine could be simulated by a chemical reaction network with a small probability of error. Although not surprising, this result is in sharp contrast to the discrete semantics of reaction systems which are not Turing complete without either the tolerance of a small probability error [17], or the addition of other mechanisms such as the unbounded dynamic creation of membranes [2,38,9], or the presence of polymerization reactions on an infinite universe of polymers [10] or DNA stacks [40].…”
Section: Definition 2 ([48])mentioning
confidence: 83%
“…The annihilation reactions (which play no role in the computability but in the complexity only) are implemented with a sufficiently large rate constant called fast, instead of with a large polynomial. The approximation error is not computed since we are not interested in the precision of the result and assume to know in advance some time horizon sufficient to get the results 10 .…”
Section: Compilation Of Gpac-generable Functionsmentioning
confidence: 99%
“…Trying to determine if network generation will terminate is equivalent to trying to solve the famous halting problem. Rule-based modeling systems have been shown to be Turing complete [113], and for such systems, the halting problem is known to be undecidable. In cases where indirect methods are inapplicable, direct methods, which are specialized for simulation of rule-based models, are used.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical computing comprises molecular recognition, transformation, as well as some control activities, e.g., activation and inhibition of pathways, that largely resound constructs in traditional programming languages. The question about the relationship between biochemical computation and Turing completeness has attracted a lot of interest, e.g., [12], and [59,60] on the Turing universality of DNA computing by reduction to grammars systems and specific classes of cellular automata. Several results prove universality of bio computation, others strive to define suitable theoretical model for what appears to be more suitably described as a reactive and distributed system, than a conventional Turing machine.…”
Section: Semi-synthetic Minimal Cells (Ssmcs)mentioning
confidence: 99%